The double burden of maldistribution: a descriptive analysis of corporate wealth and income distribution in four unhealthy commodity industries. Issue 2 (15th March 2023) - Wood, Benjamin; McCoy, David; Baker, Phil; Williams, Owain; Sacks, Gary
ABSTRACT: The health and ecological harms created and spread by firms active in many unhealthy commodity industries (UCIs) have received considerable attention from the public health community. However, less focus has been paid to analysing the distribution of wealth and income – important social and economic determinants of health – by these industries. This study aimed to examine long-term trends in wealth and income distribution by publicly listed corporations active in four UCIs: fossil fuels; tobacco; ultra-processed foods; and alcohol. Quantitative analysis of a range of data was conducted for firms listed on stock exchanges in the United States (US). Wealth and income distribution metrics were analysed at the industry level, including effective corporate tax rates and shareholder value ratios. The equity ownership structures and investor location of 20 of the largest firms were also explored. Since the 1980s, US-listed firms in the examined UCIs have distributed much less of their wealth and income to governments and much more to shareholders and investors mostly based in high-income countries. The study provides evidence that firms active in UCIs create a ' double burden of maldistribution' : their externalised social and ecological harms disproportionately affect disadvantaged population groups and governments in low- and middle-income countries; whilst, simultaneously, they are increasingly transferring wealth and income to a group over-represented by a small and privileged elite. The identified distributive injustice warrants increased policy attention.